c.3 - Dhar, Biswajit (New Delhi, 2000)
To discuss issues relevant and related to the Global Trade System and Development.To discuss and undertake research on all social, economic, morar and other issues arising out of the global economic and social orde including such matters arising out of multilateral and bilateral negotiations, deliberations and discussions.
Keywords: Bare acts